Prototype Palang Pintu Perlintasan Kereta Api Otomatis Menggunakan Komunikasi LoRa RFM95 - Sucahyo, Febrianto Eko; Dirgantara, Wahyu; Sari, Resi Dewi Jayanti Kartika (Fakultas Teknik, 2024)
Railway crossing doors are railway facilities or infrastructure to protect train travel and provide warnings to road users. This prototype automatic railway crossing door bar uses Arduino Nano, LoRA RFM 95, 5 kg Load Cell, MG996R Servo Motor, LED, and Buzzer. In component testing, there are Load Cell, LoRa RFM 95, and MG996R Servo Motor tests. In LoRa RFM 95 testing succeeded up to a distance of 350 meters, more than that distance failed to transmit signals, tests such as RSSI, SNR and Delay were also carried out on lora testing in obtained slave results 1 data produced -34 to - 104 (dBm) at a distance of 0 - 350 meters and slave 2 data produced (-32 to - 107) (dBm) at a distance of (0 - 350) meters but at a distance of 400 - 450 but each slave could not send, SNR on slave 1 has 8 data including (9.50 – 4.50) dB and slave 2 (9.50 – 3.00) dB which are relatively down and the delay from delivery depends on the distance and delivery obstacles. MG996R Servo Motor test showed error (0.07%). Load cell testing showed errors in Slave 1 (0.27%), Slave 2 (0.07%), and Master (0.20%). As well as on testing the overall system shows success as well as in opening or closing the door bars can work appropriately. Keywords: Railway Crossing Gate, Train, Infrastructure, Facilities